Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1007/s005860100251
|View full text |Cite
|
Sign up to set email alerts
|

Laminar hook instrumentation in the cervical spine. An experimental study on the relation of hooks to the spinal cord

Abstract: Several anterior and posterior methods are today available for stabilization of the cervical spine. Factors such as level and degree of instability, method of decompression, bone quality, length of fixation and safety factors influence the choice of method for a particular patient. The use of laminar hooks in the cervical spine has been restricted by fear of cord compression with the potential of tetraplegia. The aim of the present study was to assess the safety and determine the anatomical relation between ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Perioperative blood transfusion was not needed. The number of segments fused averaged 5±3 (range [2][3][4][5][6][7][8][9][10][11][12][13][14]. For fusion within the region from skull to C7, an average of 4±2 segments were fused, whereas the average number for the cervicothoracic junction was 8±3 segments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perioperative blood transfusion was not needed. The number of segments fused averaged 5±3 (range [2][3][4][5][6][7][8][9][10][11][12][13][14]. For fusion within the region from skull to C7, an average of 4±2 segments were fused, whereas the average number for the cervicothoracic junction was 8±3 segments.…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent clinical-neurophysiological study [4] in cadavers (without spinal stenosis) showed that cervical CCD hooks can be used with safety and reliability without neurologic complications during and after surgery. One cadaveric study [14] showed a close anatomical relationship with the dura and spinal cord, with a mean cervical CCD hook intrusion into the spinal canal of 27% of the diameter; however, they found no evidence of deformation of the spinal cord.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a recent experimental study with Cotrel Dubousset Instrumentation, Fagerström et al [3] found no evidence of deformation of the spinal cord in a study of 80 hook sites. Deformation of the dura was observed at four hook sites, and at two of them the hooks were in contact with the spinal cord, but without deformation of the cord.…”
Section: Discussionmentioning
confidence: 95%
“…In an experimental study of the cervical spine, Fagerström et al [12] reported on the relation between sublaminar hooks and the neuraxis, and found no evidence of spinal cord deformation exerted by sublaminar hooks, although the safety margin was limited. Pham et al [30] reported good results of cervical CDI in a series of 30 patients with RA.…”
Section: Introductionmentioning
confidence: 99%